Directional thermophysical, ablative and compressive behavior of 3D carbon/carbon composites. Issue 8 (September 2015) - Farhan, Shameel; Wang, Rumin; Li, Kezhi
Abstract: Three-dimensional carbon/carbon (C/C) composites with an apparent density higher than 1.84 g/cm 3 were fabricated using multiple carbon fiber tows oriented in four directions and densified using a combined process. This consists of a pre-densification step using a thermal-gradient chemical vapor infiltration process followed by pitch impregnation/carbonization cycles carried out under high pressure. The samples were machined along X -, Y - and Z -axis of the preform architecture denoting the weakest to the strongest direction in the composite respectively. The Y -directional sample showed the highest thermal diffusivity and the lowest CTE values. The directional ablative behavior was studied using plasma arc testing on a Huels type arc-heater. The Z -directional sample showed the lowest ablation and erosion rates while the other two showed a discrepancy in the linear and calculated erosion rates. To further investigate it, the samples after the test were analyzed in the heat-affected zone for a reduced density. Based on empirical correlation, a new term called "corrected linear ablation rate" has been formulated which also helped in the calculation of surface roughness after the ablation testing. Compressive tests were performed before and after plasma testing. After plasma testing, the compressive strength and modulus were almost the same except for the X -directional sample whose modulus reduced to 50%. The X -directional sample, being the weakest direction, showed a double shear type failure, while the other two failed with end crushing, resulting from the different fiber architecture.